2009
DOI: 10.1002/app.30134
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of poly(L‐lactide) by melt blending with rubbers

Abstract: Poly(L‐lactide) (PLA) was melt‐blended with four rubber components—ethylene–propylene copolymer, ethylene–acrylic rubber, acrylonitrile–butadiene rubber (NBR), and isoprene rubber (IR)—in an effort to toughen PLA. All the blend samples exhibited distinct phase separation. Amorphous PLA constituted a topologically continuous matrix in which the rubber particles were dispersed. According to Izod impact testing, toughening was achieved only when PLA was blended with NBR, which showed the smallest particle size in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
129
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(137 citation statements)
references
References 51 publications
8
129
0
Order By: Relevance
“…Ltd (Shenzhen, China), the selected grade is an extrusion material; it was dried at 70˚C for 6 h before using. Low density polyethylene (LDPE) (SABIC ® LDPE2308TN00) [density = 0.924 g/cm 3 , MFI = 7.5 g/10 min (190˚C/2.16 Kg)] was supplied by Sabic (KSA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ltd (Shenzhen, China), the selected grade is an extrusion material; it was dried at 70˚C for 6 h before using. Low density polyethylene (LDPE) (SABIC ® LDPE2308TN00) [density = 0.924 g/cm 3 , MFI = 7.5 g/10 min (190˚C/2.16 Kg)] was supplied by Sabic (KSA).…”
Section: Methodsmentioning
confidence: 99%
“…PLA have been blended with rubbers [3], thermoplastic starch (TPS) [4][5][6][7][8][9], poly(butylene succinate) (PBS) [10], poly(butylene succinate adipate) (PBSA) [11], poly(butylene adipateco-terephthalate) (PBAT) [12][13][14][15], acrilontryl-butadienestyrene (ABS) [16], polypropylene (PP) [17][18][19], and polystyrene (PS) [20,21], to obtain materials with lower cost and improved properties.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, diameters of the fibrils are much bigger due to overloading of HNTs and there exist a mismatch between the stretching of PA11 and HNTs alignment during the tensile deforma- Table 4 shows the notched and un-notched Charpy impact strength of PLA/PA11 blend and its nanocomposites. PLA is known for its brittle characteristics; therefore, toughening agents are widely used to enhance the PLA impact strength [35][36][37]. Considering the tensile elongation at break results, PA11 may be expected to be a good candidate for blending with PLA to increase the PLA toughness.…”
Section: Tensile Behaviormentioning
confidence: 99%
“…This impedes its applications in some areas particularly like packaging materials. 37,38 Recently, the authors have reported the use of as-synthesized hydrolytically degradable P[CL-co-LA] copolymers as effective biodegradable impact modifiers for PLA. 39 Directly related to a control over the rubbery character of the dispersed phase and the morphological features of resulting blends, an optimum toughening effect was reached using a P[CL-co-LA] copolymer at a relative molar content of 28 mol%LA.…”
Section: Introductionmentioning
confidence: 99%